(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2023)
Aquaculture nutrition has grown significantly in recent years, and the major investment in feed is focused on the nutritional improvement of the main aquaculture species of commercial interest globally, such as Oreochromis niloticus (Tilapia del Nile). Among the main countries dedicated to its production are several in Latin America, due to its warm waters of 31 to 36 º C, have omnivorous eating habits, this varies according to their life cycle phase for which have been used various flours of vegetable origin that provide the nutrients required by the species and lead to the reduction of the use of fishmeal. The objective of this review was to analyze information from 2016 - 2022 on alternative foods used in the cultivation of O. niloticus in Latin America. The analysis identifies several plant raw materials that are native plants, in some cases medicinal and other commercial that may be considered for their results as possible ingredients to be used within the diet of O. niloticus because they do not alter the digestive biochemistry or the metabolic pathway of the various nutrients while generate an increase in weight and do not affect the productive parameters.